Can the Contents of Biogenic Amines in Olomoucké Tvarůžky Cheeses Be Risky for Consumers? - Samková, Eva; Dadáková, Eva; Matějková, Kateřina; Hasoňová, Lucie; Janoušek Honesová, Simona (Foods (Basel, Switzerland), 2025)
Smear-ripened cheeses are fermented dairy products characterised by an increased content of biogenic amines (BAs). The high contents of these bioactive compounds can negatively affect consumers. The study aimed to observe the contents of BAs and po-lyamines (PAs) in Olomoucké tvarůžky cheeses depending on selected factors (year, batch, ripening/storage time, shape, weight, specific surface area, acidity, and salt content). The results showed that the variability was explained primarily by the batch (83% for the sum of BAs) and by the year (63% for the sum of PAs). The storage time significantly influenced the contents of putrescine, cadaverine, spermidine, and spermine (the explained variability was only 1-3%). The total BA contents negatively correlated with weight (r = -0.6374; p < 0.001) and positively with specific surface area (r = +0.4349; p < 0.001). A negligible positive correlation coefficient was found between the total BAs and pH (r = +0.1303). A low negative correlation was also found between the total BAs and salt content (r = -0.1328). Compared to previous studies, the total average BA contents were considerably low. In conclusion, this type of cheese does not represent a serious problem for most consumers.
Keywords: storage; biogenic amines; smear-ripened cheeses; batch; salt content; active acidity; polyamines; shape